Resenha de "Producing Presences" - Mandagará, Pedro (Letrônica, 2008)
Resenha de MENDES, Victor K.; ROCHA, João Cezar de Castro (Eds.). Producing Presences: branching out from Gumbrecht’s work. Dartmouth, Massachusetts: University of Massachusetts Dartmouth, 2007. (Adamastor book series, 2)